2017
DOI: 10.1111/mcn.12499
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Peoples' food systems, nutrition, and gender: Conceptual and methodological considerations

Abstract: Indigenous Peoples, especially women and children, are affected disproportionately by malnutrition and diet-related health problems. Addressing this requires an investigation of the structural conditions that underlie unequal access to resources and loss of traditional lifestyles and necessitates inclusive approaches that shed light onto these issues and provide strategies to leverage change. Indigenous Peoples' food systems are inextricably connected to land, which in turn is interwoven with issues of self-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 36 publications
0
66
0
3
Order By: Relevance
“…The strengths of this study are its design and direction by Kahnawakehró:non researchers and its honouring of Kanien'kehá:ka methodologies. It reiterates the value of food security research based on Indigenous perspectives (Elliott et al, 2012;Lemke & Delormier, 2017). It is important for Indigenous communities to create knowledge oriented toward their goals for self-determination (Chilisa, 2012;Smith, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strengths of this study are its design and direction by Kahnawakehró:non researchers and its honouring of Kanien'kehá:ka methodologies. It reiterates the value of food security research based on Indigenous perspectives (Elliott et al, 2012;Lemke & Delormier, 2017). It is important for Indigenous communities to create knowledge oriented toward their goals for self-determination (Chilisa, 2012;Smith, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Consensus-based decision-making is a hallmark of Haudenosaunee governance (Horn-Miller, 2013). In practice, our team reached agreement through discussion on the purpose, study design, data interpretation, and findings (Delormier, McComber, & Macaulay, 2015;Hovey, Delormier, McComber, Lévesque, & Martin, 2017). Our methodology values community member's view points as the source of identifying ways to support self-determination and fortify community strengths and wellbeing (Chilisa, 2012;Smith, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations reflect the importance that Indigenous Peoples place on continued access to the land of their ancestors, and how essential it is to develop food sovereignty based in human rights and the human right to food (Kipuri, ). For Indigenous Peoples, this is the bedrock foundation of food and nutrition security (Damman, Kuhnlein, & Erasmus, ; Lemke & Delormier, ).…”
Section: The Importance Of Nature‐human Connection For Well‐beingmentioning
confidence: 99%
“…Four basic principles characterize this balance in matriarchal societies: (a) the economy is mutual among women and men with various ways of sharing—for example, through gift exchange; (b) kinship is matrilineal (disposition of resources through generations of the maternal line) and matrilocal (couples reside with the woman's family) with gender equality, but with mothers at the family centre; (c) political decision‐making in communities is by consensus, often by a council of male designates from families; (d) broad spirituality is expressed for divinity in the entire ecosystem. Further descriptions of gender‐based societies can be found in the article by Lemke and Delormier (). These principles have been reflected upon in several ways within the research reported in this special issue.…”
Section: Introductionmentioning
confidence: 99%